Efektivitas Pemeriksaan Serologis Sifilis - Baguna, Tirsa; Niode, Nurdjannah J.; Pandaleke, Herry E. J. (e-CliniC, 2021)
Abstract: High prevalence of syphilis can be reduced by doing screening. Tests used for screening and diagnosis of syphilis are serological tests of syphilis consisting of nontreponemal tests and treponemal tests. Nontreponemal tests consist of Rapid Plasma Reagin (RPR) and Venereal Disease Research Laboratory (VDRL) meanwhile Treponemal tests consist of Treponema Pallidum Haemagglutination Assay (TPHA) and Treponema Pallidum Rapid (TP Rapid). This study was aimed to determine the effectiveness of syphilis serological tests. This was a literature review study using the keywords namely serology OR serological OR serologic AND syphilis in PubMed and ClinicalKey. The literatures were written in English and/or Indonesian, published in the last 10 years (2011-2020), and can be accessed in full text. The results obtained 25 literatures. High sensitivity was found in RPR of 9.1%-100%, VDRL of 44.4% -100%, and TP Rapid of 50.0%-100%. High specificity was found in TPHA of 99.7% and TP Rapid of 85.3% -100%. In conclusion, effective syphilis screening is performed with RPR and VDRL, while effective syphilis diagnostic is performed with TP Rapid and TPHA.Keywords: syphilis, serology tests, effectiveness of testsÂ Â Abstrak: Prevalensi kasus sifilis yang tinggi dapat diturunkan dengan adanya skrining. Pemeriksaan yang digunakan untuk skrining dan diagnosis sifilis ialah pemeriksaan serologis sifilis, terdiri atas pemeriksaan serologis non spesifik treponema dan pemeriksaan serologis spesifik treponema. Pemeriksaan serologis non spesifik treponema antara lain Rapid Plasma Reagin (RPR) dan Venereal Disease Research Laboratory (VDRL). Pemeriksaan serologis spesifik treponema antara lain Treponema Pallidum Haemagglutination Assay (TPHA) dan Treponema Pallidum Rapid (TP Rapid). Penelitian ini bertujuan untuk mengetahui efektivitas pemeriksaan serologis sifilis. Jenis penelitian ialah literature review menggunakan kata kunci serology OR serological OR serologic AND syphilis di PubMed dan ClinicalKey. Literatur yang digunakan memiliki bahasa Inggris dan/atau bahasa Indonesia, terbitan 10 tahun terakhir (2011-2020), dan dapat diakses teks lengkap. Sensitivitas tinggi ditemukan pada RPR sebesar 9,1%-100%, VDRL sebesar 44,4%-100%, dan TP Rapid sebesar 50,0%-100%. Spesifisitas tinggi ditemukan pada TPHA sebesar 99,7% dan TP Rapid sebesar 85,3%-100%. Simpulan penelitian ini ialah skrining sifilis efektif dilakukan dengan RPR dan VDRL, sedangkan diagnostik sifilis efektif dilakukan dengan TP Rapid dan TPHA.Kata kunci: sifilis, pmeriksaan serologis, efektivitas pemeriksaan